Conformity Test of Reference Air Kerma Rate (RAKR) for Brachytherapy Device in Radiotherapy Sub-Installations of Central General Hospital Prof. Dr. I.G.N.G. Ngoerah - Jaya, I Putu Wesa Angga; Ratini, Ni Nyoman; Anggarani, Ni Kadek Nova; Irhas, Rozi (Syntax Literate, 2025)
Brachytherapy requires accurate dosimetry to ensure patient safety and treatment efficacy. The Reference Air Kerma Rate (RAKR) is a key parameter in the Treatment Planning System (TPS) that quantifies the strength of radioactive sources. This study aims to evaluate the conformity between RAKR values certified by the manufacturer and those measured using a Well-Type Ionisation Chamber at the Radiotherapy Sub-Installation of Central General Hospital Prof. Dr. I.G.N.G. Ngoerah. Measurements were conducted from December 2023 to March 2024 using a SAGINOVA/ECKERT ZIEGLER brachytherapy unit. The RAKR values were obtained through electrometer readings, adjusted for air density, and compared to the manufacturer’s certification using established equations. The results were assessed using the ±3% tolerance threshold set by AAPM Report No. 46 (1994). The measured RAKR values consistently showed negative deviations from the certified values: -1.96 %, -2.69 %, -2.53 %, and -2.42 %, all within the acceptable ±3% limit. This supports the conformity and operational integrity of the device. These findings confirm that short-term RAKR measurements at the hospital align with certification values, ensuring reliable dose delivery for brachytherapy. Future research should investigate long-term calibration stability and the impact of environmental factors to refine quality assurance protocols.